Prevalence Of Insulin Resistance and Its Correlation with Fatty Liver Index In Overweight Non-Diabetic Patients - Aamir. A, Suhail; Govindaraj, Vimalkumar Anandan; Vasanthakumar, Vikrannth; Ganapathy P, Gowtham; Chandu, Gada Kanaka Durga; Kalappan, Mahendra Kumar (South Eastern European Journal of Public Health, 2025)
Introduction: The increasing prevalence of both obesity and type 2 diabetes due to easy access to high calorie foods and sedentary lifestyles resulted in NAFLD to be one of the ,major public health concern in India. Due to the asymptomatic nature of NAFLD, imaging techniques like ultrasonography and CT scan have been used as diagnostic tool though liver biopsy is gold standard test. Inspire of this, non-invasive algorithms like fatty liver index have been used nowadays in clinical as well as community to detect fatty liver. The current study aimed to determine the diagnostic accuracy among overweight non-diabetic patients. Methods: An observational cross sectional study was conducted in a internal medicine department of tertiary care center situated in South India between 2022 to 2023 .Convenient sampling technique was followed. A structured questionnaire was used to collect data on socio-demographic and relevant clinical details. Fatty liver index was enumerated with waist circumference, Body Mass Index, serum triglycerides and gamma glutaryl transferase. Ultrasonography was performed as diagnostic test. Results: A total of 107 study subjects were included. Majority of the study subjects were in age category of 40-60 years (66%). Both male and female genders were equal in number. The prevalence of non alcoholic fatty liver disease identified by fatty liver index was 57 % whereas by ultrasonography it was 54.2%. The sensitivity and specificity of fatty liver index validated against ultrasonography were 77.1% and 76.1% respectively. Conclusion: Fatty liver index has been found to be acceptable diagnostic tool which could be used especially when imaging techniques are not available.